Pruning of plum trees and maintenance of balanced yielding - Gonda, I. (International Journal of Horticultural Science, 2007)
In this review, we give an overview of the pruning techniques that should be applied in commercial plum orchards. First, a detailed description of pruning for shaping the different crown types for the first, second, third, fourth and fifth years and the phytotechnical works is given for crowns with a circular projection area. Then, pruning for open crowns forms, such as the vase form is discussed. Following the shaping of the crown, it should be maintained by pruning. Detailed information is given on pruning for maintenance with special emphasis on the comparison of winter and summer pruning. In the following part of the manuscript, pruning experience is described separately for the major commercial plum cultivars in Hungary such as Cacanska lepotica, President, Bluefre, Stanley. Recommendations for cultivation systems under non-irrigated conditions are also included. Finally, light requirements, growth characteristics and suggested crown forms of the different cultivars are described for cvs. Ageni, Althan Tingle), Besztercei szilva Nm. 122, Bluefre, Cacanska lepotica, Cacanska rodna, Debreceni muskotály, Montfort, President, Ruth Gerstetter, Sermina, Stanley, Tuleu gras and Zöld ringló).